Сказка о золотом петушке - Пушкин Александр Сергеевич (Хорошие книжки для малыша и малышки, 2017)
Экземпляры: ф.13 (20171121) / Инвентарный номер: 54284 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: П 91 / ББК: 84(2Рос=Рус)1